The influence of leverage and public accounting firm reputation on audit delay with the moderating variable of company complexity - Herdiyanti, Reza Ayu; Suryaningsum, Sri; Zuhrotun, Zuhrotun (Proceeding International Conference on Accounting and Finance, 2026)
This study aims to determine the effect of leverage and PAF reputation on audit delay with company complexity as a moderating variable in energy sector companies listed on the IDX for the period 2022-2024. Of the 90 companies, 64 companies that met the criteria were selected, resulting in a total of 192 observations. The analysis was conducted quantitatively using SPSS with a multiple linear regression model and moderation regression analysis, after the data underwent classical assumption testing. The results show that PAF reputation has a negative effect on audit delay, while leverage has no effect on audit delay. Furthermore, company complexity strengthens the positive effect of leverage on audit delay, while company complexity cannot moderate the effect of PAF reputation on audit delay. This study differs from previous studies because it uses company complexity as a moderator variable, which has rarely been studied. In addition, this study uses the latest data (2022-2024), which reflects the post-pandemic situation and the latest OJK regulations.